The house of sixty fathers - De Jong, Meindert; Sendak, Maurice; De Jong, Meindert (New York: Harper Trophy, 1956)
Alone in a sampan with his pig and three ducklings, a little Chinese boy is whirled down a raging river, back to the town from which he and his parents had escaped the invading Japanese, and spends long and frightening days regaining his family and new home.
In dust jacket.
LC copy is signed by the author.
Keywords: World War, 1939-1945 -- Juvenile fiction